Melipona scutellaris geopropolis: chemical composition and bioactivity - Coutinho, Sónia (2014)
Geopropolis has been used in traditional medicine for centuries. In this study, the botanical origin, physicochemical profile, and biological activities of geopropolis from Melipona scutellaris harvested during rainy and dry seasons were investigated. Palynological analysis identified over 50 pollen types, with Schinus terebinthifolius and Cecropia being the predominant types. The analytical results were in line with those reported in the literature. Rainy-season geopropolis exhibited higher total phenol and flavonoid content (determined using High Performance Liquid Chromatography-25.13% and 3.92%, respectively) compared to the dry season (19.30% and 2.09%); the major peaks (naringin, gallic acid, and catechin) were similar among samples. Antioxidant capacity was assessed via DPPH, reducing power, and beta-carotene/linoleic acid discoloration assays. Rainy-season samples displayed superior antioxidant activity across methods. Antimicrobial effects were determined using microdilution, while the impact on the cholinesterase enzyme was quantified using 5-thio-2-nitrobenzoic acid accumulation. Anti-inflammatory and antimutagenic activities were assessed through hyaluronidase enzyme inhibition and by utilizing Saccharomyces cerevisiae ATCC-20113 cells. Both samples exhibited anti-inflammatory and antimutagenic properties. Moreover, a significant inhibition of acetylcholinesterase was observed, with IC50 values of 0.35 mu g/mL during the rainy season and 0.28 mu g/mL during the dry season. Additionally, the geopropolis displayed antimicrobial activity, particularly against Staphylococcus aureus. These findings suggest the therapeutic potential of M. scutellaris geopropolis in the context of inflammatory, oxidative, and infectious diseases.